Effect of lansoprazole on quality of life in adolescents with recurrent abdominal pain - Sri Yanti Harahap; Selvi Nafianti; Sri Sofyani; Supriatmo Supriatmo; Atan Baas Sinuhaji (Indonesian Pediatric Society, 2013)
Background Recurrent abdominal pain (RAP) is one of the mostcommon complaints in adolescents. Treatment for RAP dependson the etiology. Lansoprazole has been shown to be effective ongastroesophageal reflux disease (GERD), but further study isneeded to assess the effects of lansoprazole on RAP.Objective To assess quality of life (QoL) of RAP patients whoreceived lansoprazole compared to placebo treatment.Methods This randomized, clinical trial was conducted in theSecanggang District, Lan gkat Regency, North Sumatera, fromAugust to October 2009. Patients who met the Apley criteria forRAP diagnosis were enrolled in the study. Subj ects were dividedinto two groups: those who received 30 mg lansoprazole daily andthose who received placebo, for 14 days. Quality oflife was assessedusing the Pediatrics Quality of Life (PedsQL) version 4.0 beforeadministration oflansoprazole/placebo and reassessed 30 days aftertreatment. Efficacy of treatment was assessed by comparing theQoL before and after treatment in the two groups.Results A total of 98 adolescents, aged 12 - 18 years, wereenrolled in the study and divided into two groups: lansoprazoleand placebo. There was no significant difference QoL in physicalhealth (mean differences 95%CI -109.19 to 1.02; P=0.054),emotional health (mean differences 95%CI -29.26 to 45.48;P=0.666), social functioning (mean differences 95%CI -42.91to 31.69; P=0.766), and sch ool functioning (mean differences95%CI -56.97 to 24.32; P= 0.430), before and after treatmentin the two groups.Conclusion There is no significant difference in QoL between thetwo groups of adolescents with RAP before and after lansoprazoletreatment.